Magnetic fullerenes inside single-wall carbon nanotubes - Simon, Ferenc; Kuzmany, Hans; Nafradi, Balint; Fehér, Titusz; Forro, Lásló; Fülöp, Ferenc; Janossy, András; Korecz, Laszlo; Rockenbauer, Antal; Hauke, Frank; Hirsch, Andreas; Hauke, Frank (Physical Review Letters, 2006)
C59N magnetic fullerenes were formed inside single-wall carbon nanotubes by vacuum annealing functionalized C59N molecules encapsulated inside the tubes. A hindered, anisotropic rotation of C59N was deduced from the temperature dependence of the electron spin resonance spectra near room temperature. Shortening of the spin-lattice relaxation time T1 of C59N indicates a reversible charge transfer toward the host nanotubes above ∼350K. Bound C59N-C60 heterodimers are formed at lower temperatures when C60 is coencapsulated with the functionalized C59N. In the 10-300 K range, T1 of the heterodimer shows a relaxation dominated by the conduction electrons on the nanotubes. © 2006 The American Physical Society.